Using translation-based CI to read Latin literature. Issue 39 (2019) - Carter, David
Abstract : Krashen's Comprehensible Input theory proposes that we acquire language when the brain understands messages. The practical question then arises: how do we make the foreign words in the message comprehensible to the brain?